TINJAUAN TEOLOGIS TERHADAP BUDAYA PATRIARKAL DI INDONESIA - Eka Kristining Rahayu (Sekolah Tinggi Alkitab Tiranus, 2019)
Indonesia is one of the nation that adhere to patriarchal culture. This article is going to study the influence of patriarchal culture and its impact on women in the Indonesian society. In this study, a theological review on the culture will be conducted to observe its positive and negative aspects for women in Indonesia, and to find out the Bible’s view on the role of women in the context of patriarchal system. This article will conduct a literature study on important writings that could support this research. The result of this study explains that, theologically, patriarchal culture has positive and negative impact on women. In terms of the Bible, even though it was written in the context of patriarchal culture, it considers women as special creatures that have special roles